Point break [videorecording (DVD)] - Core, Ericson; Ramírez, Édgar, 1977-; Bracey, Luke, 1989-; Winstone, Ray, 1957- (Warner Home Video, 2016)
A young FBI agent, Johnny Utah, infiltrates a cunning team of thrill-seeking elite athletes, led by the charismatic Bodhi. The athletes are suspected of carrying out a spate of crimes in extremely unusual ways. Deep undercover, and with his life in imminent danger, Utah strives to prove they are the architects of this string of inconceivable crimes.